Pulping and papermaking properties of three tropical pines from provenance trials - Palmer, E; Plumptre, R; O'Brian, M; Quilter, T; Slater, J (Oxford Forestry Institute, University of Oxford, 1995)
The Project complements provenance studies of tropical pines reported in detail in Birks and Barnes (1990). Twelve mm cores were taken at breast height from trees in selected provenance trials and micropulped using approximately 50 gm. samples from 140 trees covering the provenances detailed in Table 1, planted at one or more of the three sites described in Table 2. Tables 23 and 24 summarise the number of trees sampled for each provenance and planting site and show the pulping qualities of the different provenances planted at the three sites, two in Brazil and one in South Africa.